The Modern Mutual Fund Family - Dannhauser, Caitlin D.; Spilker, Harold D. (Journal of Financial Economics, 2023)
Modern mutual fund families include more than active mutual funds (AMFs). AMFs in families with greater index mutual fund (IMF) presence generate higher category-adjusted gross returns. Performance is positively related to the levels of passive and active fees, suggesting moral hazard. Intrafamily competition from IMFs in the same Morningstar category incentivizes managers to exert effort. Financial resources do not contribute to the performance effect. Cross-trading with IMFs occurs with some positive effect on performance. ETFs have no impact on performance. IMFs reduce flow-performance sensitivity and flow volatility of AMFs in the family. IMFs and ETFs uniquely contribute to expense pressure.